La moda de la distopía anticapitalista en la obesa narrativa audiovisual contemporánea vía streaming: el lenguaje de la crueldad mediante el caso de la serie El juego del calamar (Monográfico) - Fernández Rodríguez, Carlos (2022)
Torture porn, constant references to Italian Giallo or exploitation cinema, anti-capitalist messages, the dystopian fashion in audiovisual narratives and the popularisation and definitive settlement of streaming platforms due to the COVID-19 pandemic, have given rise to the establishment of a new fashion: the tendency of an audience to enjoy spectacularised cruelty disguised as political sermons. Far from trying to censor such works, the aim is to promote reflection that continues to induce a sense of cynicism and abandonment of the citizenry by their rulers, which the audiovisual entertainment industry seems to take advantage of by groping the sense of general disenchantment in the West. In the midst of this ecosystem appears the recent Netflix series The Squid Game, a festival of sadistic imagery with deep political overtones that brings together several of the aforementioned genres and thematic axes in a single product. Consequently, the main objective is to analyse the characteristics of the fashion for narratives of this type, through a content analysis of the series The Squid Game in order to inspect the elements that configure some key elements of mainstream entertainment via streaming. As a result, the plots are predictable and cold, but the audiovisual imagination is fresh and attractive, so that the anti-capitalist background is perceived in the background.